Correction: Tiwari et al. Neuroprotective Effect of α-Mangostin in Ameliorating Propionic Acid-Induced Experimental Model of Autism in Wistar Rats. Brain Sci. 2021, 11, 288 - Aarti Tiwari; Rishabh Khera; Saloni Rahi; Sidharth Mehan; Hafiz Antar Makeen; Yahya H. Khormi; Muneeb U Rehman; Andleeb Khan (Brain Sciences)
Missing Supplementary Materials: [...]